1988
DOI: 10.1016/s0022-5347(17)42864-3
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected Prostatic Adenocarcinoma in Patients Who Have Undergone Radical Cystoprostatectomy for Transitional Cell Carcinoma of The Bladder

Abstract: In 45 of 165 male cystectomy patients with bladder cancer (27 per cent) incidental adenocarcinoma of the prostate was found during the diagnostic evaluation or histological examination of the cystoprostatectomy specimens. Of the patients 37 had stage A1 or A2 and 8 had stage C or D1 prostate cancer. Clinical presentation, stage and grade distributions for each primary and prognostic variable are reviewed. Over-all, 67 per cent of the patients currently are alive with a 3-year actuarial survival rate of 60 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
2
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 7 publications
6
31
2
3
Order By: Relevance
“…Incidental prostate carcinoma rates detected in cases having undergone RCP due to bladder tumor vary between 4% and 60% (Table 2) (2,6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). One of the reasons for these various rates has been linked to the use of section intervals in different widths.…”
Section: Discussionmentioning
confidence: 99%
“…Incidental prostate carcinoma rates detected in cases having undergone RCP due to bladder tumor vary between 4% and 60% (Table 2) (2,6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). One of the reasons for these various rates has been linked to the use of section intervals in different widths.…”
Section: Discussionmentioning
confidence: 99%
“…İnvaziv mesane kanseri nedeniyle RSP yapılmış hastaların incelendiği çalışma-larda rastlantısal prostat kanser sıklığı %17-70 arasında değişen oranlarda rapor edilmiştir (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Yapılan çalışmalarda prostat kanseri ile mesanenin değişici epitel hücreli karsinomu arasındaki ilişki ortaya konmuş ve kontrol grubuna göre mesane kanseri olan hastalarda prostat kanseri sıklığının 9 kat arttığı gösterilmiştir (22). Chun (14) tarafından yapılan çalışmada, normal popülasyona göre riskin 19 kat arttığı rapor edilmiştir.…”
Section: Discussionunclassified
“…Yapılan bir çalışmada ameliyat öncesi parmak ile rektal muayenesi ve PSA seviyesi normal olan ve prostat koruyucu radikal sistektomi yapılan hastaların retrospektif analizinde, bu yöntemle ek onkolojik risk olmaksızın daha iyi üriner kontinans ve seksüel fonksiyon sonuçları sağladığı saptanmıştır (31). Ancak rastlantısal prostat kanser sıklığının yüksek olması, erkeklerde kanserden ölümlerde ikinci sırada yer alması ve en sık prostat apeksinin tutulması nedeniyle RSP esnasında prostat dokusunun tamamen çıkarılmasını öneren yazarların oranı daha fazladır (13,(16)(17)(18). Bununla birlikte her iki kanserin birlikte bulunmasının, her birinin tek başına bulunmasına göre prognozu değiştirmediği belirtilse de (32), erken tanının prognoza olan katkısı unutulmamalıdır (33)(34)(35).…”
Section: Discussionunclassified
“…Additionally, several studies have shown the high incidence of incidental prostate adenocarcinoma in specimens from cystoprostatectomies performed for treating bladder cancer (3,(6)(7)(8)(9). Some of them reported a predominance of tumors in the prostate apex (3,6).…”
Section: Introductionmentioning
confidence: 99%